Bone healing around nanocrystalline hydroxyapatite, deproteinized bovine bone mineral, biphasic calcium phosphate, and autogenous bone in mandibular bone defects. Issue 7 (29th November 2014) - Broggini, Nina; Bosshardt, Dieter D.; Jensen, Simon S.; Bornstein, Michael M.; Wang, Chun‐Cheng; Buser, Daniel
Abstract: The individual healing profile of a given bone substitute with respect to osteogenic potential and substitution rate must be considered when selecting adjunctive grafting materials for bone regeneration procedures. In this study, standardized mandibular defects in minipigs were filled with nanocrystalline hydroxyapatite (HA‐SiO), deproteinized bovine bone mineral (DBBM), biphasic calcium phosphate (BCP) with a 60/40% HA/β‐TCP (BCP 60/40) ratio, or particulate autogenous bone (A) for histological and histomorphometric analysis. At 2 weeks, percent filler amongst the test groups (DBBM (35.65%), HA‐SiO (34.47%), followed by BCP 60/40 (23.64%)) was significantly higher than the more rapidly substituted autogenous bone (17.1%). Autogenous bone yielded significantly more new bone (21.81%) over all test groups (4.91%–7.74%) and significantly more osteoid (5.53%) than BCP 60/40 (3%) and DBBM (2.25%). At 8 weeks, percent filler amongst the test groups (DBBM (31.6%), HA‐SiO (31.23%), followed by BCP 60/40 (23.65%)) demonstrated a similar pattern and was again significantly higher as compared to autogenous bone (9.29%). Autogenous bone again exhibited statistically significantly greater new bone (55.13%) over HA‐SiO (40.62%), BCP 60/40 (40.21%), and DBBM (36.35%). These results suggest that the osteogenic potential of HA‐SiO and BCP is inferior when compared to autogenous bone. However, in instances where a low substitution rate is desired to maintain the volume stability of augmented sites, particularly in the esthetic zone, HA‐SiO and DBBM may be favored. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1478–1487, 2015.